Association of Periodontitis and Aging-Related Diseases: A Review of Mechanistic Studies - M Gholami; SM Asadinejad; D Kakavand; P Jafari Doudaran; AH Fathi (Islamic Azad University, 2023)
Background and Aim: Periodontitis, as the most prevalent cause of tooth loss, affects 20-50% of individuals throughout the world. One factor involved in the severity and incidence of periodontitis is aging, which is a substantial risk factor for mortality and morbidity. It is stated that some disorders are common in older population, like cardiovascular diseases, osteoporosis, chronic kidney disease, and Alzheimer's disease. Understanding the changes related to aging may provide a better insight into age-related diseases. Hence, this study aimed to review and summarize evidence regarding periodontitis and aging-related disorders with a mechanistic insight.    Materials and Methods: Data were obtained from the scientific databases, including PubMed, Google Scholar, and Scopus in English between 1993 and 2021. Results: Cardiovascular diseases, osteoporosis, chronic kidney disease, and Alzheimer's disease are associated with periodontitis directly or indirectly, and pro-inflammatory cytokines are the key mediators in such relationships. For instance, interleukin (IL)-1β, tumor necrosis factor-α (TNF-α), and IL-6 have a substantial role in pathogenesis of periodontitis in the majority of such diseases. These agents, particularly IL-1β and TNF-α, can also lead to leukocyte migration and subsequently form reactive oxygen species (ROS), reactive nitrogen species, and matrix metalloproteinases (MMPs). Conclusion:  It seems that periodontitis is linked to aging-related diseases, namely cardiovascular diseases, osteoporosis, chronic kidney disease, and Alzheimer's disease by the mediation of pro-inflammatory agents such as IL-1β, TNF-α, and IL-6.